Pengaruh Model Pembelajaran Heterogeneous Group terhadap Hasil Belajar Siswa pada Mata Pelajaran Sejarah di SMK - Hazmi, Nahdatul; Destel Meri; Dedi Asmara; Diva Yulika Anugrah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The purpose of this study was to determine the influence and differences in the influence of the use of the Heterogeneous Group learning model on student learning outcomes in history subjects. This study is a quantitative study using an experimental method with a research design that is Nonequivalent Control Group Design and sampling techniques through Probability Sampling. The data analysis technique used the t-test, by conducting normality tests and homogeneity tests. The results of this study indicate: 1) there is an influence of the Heterogeneous Group learning model on student learning outcomes in history subjects with a value of t count = 6.238 and t table at a significance level of 0.05 is 2.101, meaning 6.238 > 2.101. 2) there is a difference in the influence of the Heterogeneous Group learning model with the conventional learning model (lecture) on learning outcomes. It can be concluded that there is an influence of the Heterogeneous Group learning model on student learning outcomes in the history subject of class X Marketing at SMK Negeri 1 Luak District. Keywords: Heterogeneous Group, Influence, Learning Outcomes.